2023
DOI: 10.3390/educsci13040364
|View full text |Cite
|
Sign up to set email alerts
|

Students Satisfaction with Online Higher Education during the COVID-19 Pandemic

Abstract: The digital educational environment is not new in the modern world, but in the context of the COVID-19 pandemic, the transition to online learning has become necessary and fast. This offered the possibility to study various characteristics of objects and subjects in the digital educational environment. During the pandemic, universities worldwide were forced to switch to online learning, creating a global educational experiment with results to be comprehended and theoretically reflected upon. The significance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Overall, there were lower levels of engagement compared to in-person lectures, and as Koh and Daniel [52] found, these particularly hampered less motivated students. Finally, in a large study by Arsenijević et al [56] conducted in Russia and five Balkan countries, higher satisfaction levels were associated with the active organisation and management of students' collaborative work. The need to maintain a strong social presence was found to be more important for students with level academic performance, for whom blended learning was also more successful than a fully online delivery model.…”
Section: Factor E: Growth In Online Education and Trace Data Of Stude...mentioning
confidence: 90%
“…Overall, there were lower levels of engagement compared to in-person lectures, and as Koh and Daniel [52] found, these particularly hampered less motivated students. Finally, in a large study by Arsenijević et al [56] conducted in Russia and five Balkan countries, higher satisfaction levels were associated with the active organisation and management of students' collaborative work. The need to maintain a strong social presence was found to be more important for students with level academic performance, for whom blended learning was also more successful than a fully online delivery model.…”
Section: Factor E: Growth In Online Education and Trace Data Of Stude...mentioning
confidence: 90%
“…Within the surveyed literature, some researchers position it within the CoI framework, examining the connections between cognitive, teaching, and social presence. Some researchers [55] propose a positive correlation between satisfaction with online learning and overall CoI presence, while others, such as [54], suggest that course satisfaction is predicted social and teaching presence. Some scholars, such as [53], concentrate on the CoI framework, and they have found diverse results regarding how selfregulated learning influences these presences in online satisfaction.…”
Section: Discussionmentioning
confidence: 99%
“…'Zhang et al (2019) found, for example, that timely feedback promotes student participation, as well as progress management, rational arrangement of learning, and online communication and discussions had an encouraging effect on learning. The TP has indeed been found to have also an association with students' satisfaction (see e.g., Arsenijevic et al, 2023;Kyei-Blankson et al, 2019;Tayeh, 2021). In fact, it has been discovered that the TP benefits both SP and CP, as well as indirectly on learning performance as a facilitator of students' cognitive thinking and social interaction (Law et al, 2019).…”
Section: Design Frameworkmentioning
confidence: 99%